Penyusunan Assessment For Learning dengan Menerapkan DeepSeek - Mahmuddiyah, Mahmuddiyah; Muthmainni Syarifah; Etika Zakiyah; R.A. Nurnaningsih; Ary Prasetyawati; Nurma Indah Oktaviani (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to describe the process of developing Assessment for Learning by applying DeepSeek in the context of 21st-century learning. The application of DeepSeek aims to increase the effectiveness of formative assessment through faster, more accurate, and adaptive learning data analysis to students' needs. The purpose of this study is to describe the steps of implementing DeepSeek and developing Assessment for Learning in learning at Madrasah Tsanawiyah Negeri 6 Boyolali and Madrasah Tsanawiyah Negeri 1 Klaten. This research method uses a qualitative approach. The subjects of the study were teachers at Madrasah Tsanawiyah Negeri 6 Boyolali and Madrasah Tsanawiyah Negeri 1 Klaten. The informants of this study were teachers. Data collection techniques were interviews, observation, and documentation. The results of this study are: 1) Steps for developing Assessment for Learning by utilizing DeepSeek, namely: a) determining the objectives of Assessment For Learning; b) developing assessment instruments; c) designing assessment rubrics; d) analyzing student learning outcomes; e) providing feedback; f) teacher and student reflection; 2) The stages in developing Assessment for Learning are as follows: a) Determining learning objectives, focusing on in-depth understanding and critical thinking skills; b) Analyzing learning needs with DeepSeek, using DeepSeek to identify students' difficulties and potential; c) Designing digital assessment instruments by creating questions, reflections, or assignments based on data from DeepSeek analysis; d) Implementing assessments by providing automated and personalized feedback; e) Analyzing assessment results, using DeepSeek to see patterns of learning outcomes; f) Reflecting and improving learning, using the analysis results to adjust strategies and deepen students' understanding. The conclusion of this study is that DeepSeek is able to help teachers identify students' difficulties and potential, provide real-time formative feedback, and facilitate more personalized and in-depth learning. Thus, developing Assessment for Learning based on DeepSeek not only improves the quality of evaluation but also strengthens the assessment's function as a learning tool that encourages in-depth understanding, critical thinking, and reflective learning.